2009
DOI: 10.1152/ajprenal.90642.2008
|View full text |Cite
|
Sign up to set email alerts
|

The monocyte chemoattractant protein-1/CCR2 loop, inducible by TGF-β, increases podocyte motility and albumin permeability

Abstract: The role of monocyte chemoattractant protein-1 (MCP-1) in diabetic nephropathy is typically viewed through the lens of inflammation, but MCP-1 might exert noninflammatory effects on the kidney cells directly. Glomerular podocytes in culture, verified to express the marker nephrin, were exposed to diabetic mediators such as high glucose or angiotensin II and assayed for MCP-1. Only transforming growth factor-beta (TGF-beta) significantly increased MCP-1 production, which was prevented by SB431542 and LY294002, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
110
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 39 publications
3
110
0
2
Order By: Relevance
“…Secretory factors from macrophages may cause histological and functional changes in glomeruli. For example, TGF β1 (TGFB1) and MCP1, induced in surrounding cells by or secreted directly from activated macrophages, have been shown to upregulate CTGF production [43] and increase albumin permeability in cultured podocytes [44][45][46]; we have recently reported that overproduction of CTGF specifically in podocytes is sufficient to worsen diabetic nephropathy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Secretory factors from macrophages may cause histological and functional changes in glomeruli. For example, TGF β1 (TGFB1) and MCP1, induced in surrounding cells by or secreted directly from activated macrophages, have been shown to upregulate CTGF production [43] and increase albumin permeability in cultured podocytes [44][45][46]; we have recently reported that overproduction of CTGF specifically in podocytes is sufficient to worsen diabetic nephropathy [19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to physical forces, an alternative mechanism for proteinuria could be attributable to humoral factors that are induced during the disease. For example, inflammatory cytokines or fibrogenic mediators had been shown to modulate podocyte motility and albumin permeability, mRNA expression of podocyte markers such as nephrin and ezrin as well as podocyte survival and adhesion (9)(10)(11)(12)(13)(14)(15). Presumably, through mesangial cellpodocyte communication (16)(17)(18), these effects might lead to breakdown of the glomerular permeability with resultant formation of proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines and fibrogenic mediators have been shown to modulate podocyte motility and albumin permeability in vitro (9)(10)(11)(12)(13). And mesangialderived cytokines such as tumor necrosis factor (TNF)-α or transforming growth factor (TGF)-β1 can inhibit the expression of nephrin and ezrin by podocytes and induce podocyte death and detachment (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The main function of the slit diaphragm is to form a size-selective barrier for proteins and since many of the slit diaphragm proteins are phosphorylated, this contributes to the charge-selective element (Tryggvason K, 2001). Podocyte-specific multiprotein complexes, similar to adherens junctions, extend between the filtration slits, closely interact with the actin cytoskeleton, influencing signaling pathways and motility of the podocyte (Lee et al, 2009) (Burt et al, 2007) and thereby establishing the final barrier to urinary protein loss (Somlo and Mundel, 2000). The proteins which make up the slit diaphragm system are nephrin, Neph1, Neph2, podocin, fatty acid transporter tumor suppressor homolog-1 (FAT1) and FAT2, and the calcium channel transient receptor potential cation 6 (TRPC6) and cadherins (Harita Y, 2008) (Yaoita et al, 2005) (Liu G, 2003) (Dryer SE, 2010) .…”
Section: Introductionmentioning
confidence: 99%